Efek Opini Audit dan Kepemilikan Publik terhadap Ketepatan Waktu Penyampaian Laporan Keuangan. - Zulkifli Umar; Budi Safatul Anam; Gustia Nizar (Jurnal EMT KITA, 2022)
This study aims to examine the effect of audit opinion and public ownership on the timeliness of submitting financial statements. This research is a sample study, which includes 222 companies from 547 companies in the manufacturing sector during the 2018-2020 observation year. The sample was selected by purposive sampling technique. The analytical method used is logistic regression. The results of the study found that the audit opinion had an effect on increasing the timeliness of the submission of financial statements, especially the qualified audit opinion. Public ownership also has an effect on increasing the timeliness of submitting financial reports.